Prevention Produce: A Student-Led Nutrition Education Community Intervention (P04-022-19). (13th June 2019) - Noverati, Nicholas; Chen, Yixin; Artrip, Rick; Scipioni, Anna; Yumen, Anna; Hale, David; Veldheer, Susan; George, Daniel
Abstract: Objectives: Prevention Produce is a medical student-led preventative medicine program designed with two goals in mind: (1) to supplement student volunteers' education on strategies to communicate nutrition knowledge to patients and, in doing so, (2) educate patients in the community about basic nutritional principles to have a long-lasting effect on health and wellness. Methods: Participants over age 18 were identified through multiple sources within the Penn State Health System and matched with medical students who coordinated meeting with the participant at one of three local Central, PA farmers' markets. Participants completed four visits to the market consisting of a 15–30-minute nutrition education lesson, followed by a shopping session with the student and a voucher approved for the expense of $10 per family member (up to four). A validated 60-item questionnaire to assess basic nutrition knowledge was given at the first and last meeting to assess what knowledge gaps were filled by the program. Data were collected and entered into a spreadsheet to compare pre-and post-program % correct. A focus group was held with six students to understand what was gained through participation. Conversations were recorded, transcribed and de-identified into a word-processing document. Data was then coded to identify emergent themes. Results: Mean score on questionnaires showed an increase from 42.98% pre-program to 68.42% post-program ( n  = 5). Four emergent themes identified from the focus group: The program enhanced students' professional development by allowing them to apply nutritional knowledge with a patient. Students' role as a health professional was affirmed through their patients' post-program increase in nutritional knowledge. Lastly, scheduling for patients was the largest barrier to implementing the program. Conclusions: These data suggest that students can serve as effective health educators in the community, that four short educational sessions can improve understanding of important but basic nutrition knowledge, and that this experience enriches education and practical patient communication skills for students. The sample size of this study is small but serves as a pilot for future student-led nutrition intervention initiatives. Funding Sources: The Foundation for Enhancing Communities (TFEC). The Association of Faculty and Friends ( AFF )